A Triband Planar Inverted-F Antenna with Quadratic Koch Fractal Shaped Slit Along with a Shorted Parasitic Strip - Kumar, D.; Chowdhury, D.; Ghatak, R. (Advanced Electromagnetics, 2018)
In this paper, a novel compact tri-band planar inverted-F antenna (PIFA) for mobile communication application is proposed. The antenna is capable to cover GSM 900 MHz, DCS 1.8 GHz and WLAN (IEEE 802.11b) 2.45 GHz bands. The proposed PIFA is composed of a quadratic Koch shape slit and a parasitic strip. The PIFA with the fractal shaped slit contributes to the first and second resonance while the shorted strip brings forth the third band. The impedance bandwidths of 84 MHz, 132 MHz and 81 MHz for GSM 900, DCS 1800 and WLAN (IEEE 802.11b) 2450, respectively are achieved. A realized gain of 2.44 dBi, 4.48 dBi and 3.86 dBi is obtained at 0.9 GHz, 1.8 GHz and 2.45 GHz, respectively. The proposed antenna is fabricated and |S11| dB is measured. Reasonable agreement between simulated results as well as measured results is obtained.